Molecular dynamics computations of brine-CO2 interfacial tensions and brine-CO2-quartz contact angles and their effects on structural and residual trapping mechanisms in carbon geo-sequestration - Iglauer, Stefan; Mathew, M.; Bresme, F. (Academic Press, 2012)
In the context of carbon geo-sequestration projects, brine–CO2 interfacial tension γ and brine–CO2–rock surface water contact angles θ directly impact structural and residual trapping capacities. While γ is fairly well understood there is still large uncertainty associated with θ. We present here an investigation of γ and θ using a molecular approach based on molecular dynamics computer simulations. We consider a system consisting of CO2/water/NaCl and an α-quartz surface, covering a brine salinity range between 0 and 4 molal. The simulation models accurately reproduce the dependence of γ on pressure below the CO2 saturation pressure at 300 K, and over predict γ by ~20% at higher pressures. In addition, in agreement with experimental observations, the simulations predict that γ increases slightly with temperature or salinity. We also demonstrate that for non-hydroxylated quartz surfaces, θ strongly increases with pressure at subcritical and supercritical conditions. An increase in temperature significantly reduces the contact angle, especially at low-intermediate pressures (1–10 MPa), this effect is mitigated at higher pressures, 20 MPa. We also found that θ only weakly depends on salinity for the systems investigated in this work.